PEMETAAN DAN PENINGKATAN MUTU PENDIDIKAN DALAM MATA PELAJARAN EKONOMI BERDASARKAN HASIL UJIAN NASIONAL DI KABUPATEN BENER MERIAH DAN ACEH TENGAH - Raihani, Raihani (Jurnal Mentari, 2012)
The research was motivated by the fact the results of National Examination (UN) in the District and Central Aceh highlands where the absorptive capacity of students between the Basic Competence (KD) in a subject is not the same. Certain KD has a low absorption and consistent every year. This study aims to: i) Obtain a map of the competence of high school students in the district of Central Aceh highlands and in the subjects that are the UN, ii) Assess the reasons of failure/success of students in mastering a specific competency in each subject, iii) Determine the model appropriate problem-solving to address the problem sfound. The method used is the servey with Grounded Research approach. The research was carried out in high school in the district and the highlands of Central Aceh. Each of the three school districts selected for the sample schools, namely Takengon SMA 1, SMA 3 and SMA 5 Takengon Takengon in Central Aceh district. While in the highlands district elected Bandar SMA 1, SMA 2 buckle elephant, and a high school hill. Research outputs expected are: i) Current student competence, acquired through the documentation of students´ absorption in the UN in the last 3 years on all of the sample, ii) Factors causing the students have not been able to achieve absorption of> 60% explored through in-depth interviews with teachers, wakasek curriculum, the school principal, head of administration, and students, and iii) solisi alternative offered, obtained through interviews and FGDs. The results showed consistently in the last three years, there is a problematic KD (UN absorption <60%) of each subject in the UN-in the District and the highlands of Central Aceh. The percentage of the amount of KD is problematic varies greatly, and Economics subjects as the eyes pelajarang recorded with the highest percentage of the amount of KD problematic in the District and the highlands of Central Aceh. All KD problematic in every subject which is the UN has successfully created a map of competence. Factors that cause students not yet able to achieve completeness (absorption <60%) are generally nearly equal between domonan namely: lack of facilities/infrastructure to support learning, lack of teacher competence both professional competence and pedagogic competencies, allocation of teaching time is not right, students are not skilled at analyzing and work on the problems of high level thinking skills, and mismatch. Offered alternative solutions to address the various factors that cause failure are: continuous teacher professional development (CPD) through lesson study, the correct preparation of the syllabus, to complete the facilities/infrastructure to support learning, training and workshop models of innovative learning, reinforcement learning materials, especially KD problematic, monitoring and evaluation of teacher performance on an ongoing basis by the principal and school superintendent. Keywords: mapping, competence, National Examination (UN)     DAFTAR PUSTAKA Mulyana. 2003. Kurikulum Berbasis Kompetensi (Konsep, Karakteristik dan Implementasi). Bandung: PT. Remaja Rosdakarya. Mulyasa, E. 2006. Kurikulum Tingkat Satuan Pendidkan. Bandung: PT. Remaja Rosdakarya. Bloom, B. Human Characteristics and School Learning, (New York: Mc. Grow Hill). Dimyati dan Mudjiono. 1999. Belajar dan Pembelajaran. Jakarta: Rineka Cipta. Himalik, O. 2006. Proses Belajar Mengajar. Bandung: Bumi Aksara. Idris, J. 2005. Analisis Kritis Mutu Pendidikan. Yogyakarta: Suluh Press. http://pendidikan.blogspot.com/2010/12/konsep-membuat-rumusan-indicator-hasil.html, (Diakses pada tanggal 12 Maret 2011). Dalyono. 2008. Psikologi Pendidikan. Jakarta: Rineka Cipta. Firdaus. 2005. “Faktor-Faktor Penyebab Rendahnya Minat Orang Tua untuk Melanjutkan Pendidikan Anak ke Sekolah Menengah Pertama (Studi Kasus di Sekolah Dasar Negeri Lubuk Sengkuang Kecamatan Banyuasin III Kabupaten Banyuasin)” Skripsi tidak dipublikasikan. Palembang: Universitas Sriwijaya. Gunawan, Ary H. 2000. Sosiologi Pendidikan: Suatu Analisis Sosiologi tentang Pelbagai Problem Pendidikan. Jakarta: Rineka Cipta. Tirtarahardja, Umar dan La. Sula. 2000. Pengantar Pendidikan. Jakarta: Rineka Cipta.